On Nicolai Hartmann - Juršėnas, Nikodemas (Problemos, 1996)
By 1993, the famous German thinker N. Hartmann, widely known as the creator of critical ontology (neorealism), had already formed a close friendship with V. Seseman in the Lithuanian University in Kaunas. In his letter of recommendation to the Rector of the Lithuanian University, he characterized V. Seseman as a man of talent and a creative person of great abilities. Both thinkers were in regular correspondence, arranged meetings, together, exchanged their publications and gave similar course lectures. Attention has always been paid to the personality and work of N. Hartmann in Lithuania.